Nilai-Nilai Pendidikan Moral dalam Buku Teks Siswa Mata Pelajaran Sejarah Wajib Kelas X Semester 1 SMA - Ahmad Nurhuda; Stevani Permata Sari; Suryadi Fajri (Tarikhuna: Journal of History and History Education, 2022)
This article explains the values of moral education in the form of educational moral values contained in the history books of class X students. This research uses the bibliography method with a historical approach. The results of the study indicate that there are several values including 1) Divinity values, Divinity moral values include obedience and the moral values found by researchers regarding the value of obedience. Being obedient and obedient to the rules needs to be trained and applied; 2) The moral values contained in noble character are: honesty, namely a social law which states that every human being has a tendency, to be honest, and feels guilty if he is not honest. Patience must be cultivated. Patience is an attitude that naturally must exist and be grown in anyone. Patience can be interpreted as an attitude that is not weak, enthusiastic, and does not give up easily in the face of every test or trial given by the Almighty; 3) Moral values, relating to moral values, the next is the aspect of the character. Someone who has good character or behavior is a reflection of a person who is commendable, has character, is polite, has respect, tolerance, and so on; and 4) Personality values, including some values of independence and self-confidence. Independent and confident attitude. An independent attitude reflects that a person is able to maintain everything and his existence in life.